(untitled) (Journal of Informatics and Mathematical Sciences, 2013)
Functional, integral and differential equations of transformed probability generating functions are generally recognized as powerful analytical tools for establishing characterizations of discrete probability distributions. The present paper establishes a characterization of the distribution of an important integral part model by incorporating an integral equation based on three fundamental transformed probability generating functions. Interpretations of such a characterization in analyzing and implementing information risk frequency reduction operations are also established.